Winter Wheat Variety Response to Timing and Number of Fungicide Applications During the 2019–2020 Growing Season in Kansas - G. Cruppe; B. R. Jaenisch; B. Valent; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this project was to evaluate the yield response of different winter wheat varieties to different fungicide management treatments during the 2019–2020 growing season in Kansas. Fourteen varieties were evaluated under four fungicide treatments (no fungicide, application either at jointing, heading, or at both stages) in five locations across Kansas in a split-plot design. Disease incidence was assessed approximately 20-d after each fungicide application. Septoria blotch and tan spot were the most prevalent early-season diseases at the studied fields, while stripe rust, leaf rust, and tan spot prevailed late in the season. Late-season diseases had a greater effect on grain yield when compared to early-season diseases. While varieties responded differently to fungicide management, there was an overall yield increase of 1.8 bushels per acre resulting from the jointing fungicide application; 3.3 bu/a from the heading fungicide; and 4.3 bu/a from the combination of both applications. Overall, susceptible varieties had a greater response to fungicide management compared to varieties with intermediate or high levels of genetic resistance. Late-season drought and heat stress affected three out of five locations (Belleville, Conway Springs, and Hutchinson planted late), resulting in less effect of fungicide management than in the other two locations (Ashland Bottoms and Hutchinson planted in the optimal timing). Although there were some similarities, the ranking of the highest yielding varieties was not uniform across locations. Our preliminary data suggest that the application of fungicide to winter wheat in Kansas might be advantageous, but the degree of this benefit will depend upon the environment and on the variety.
Keywords: wheat; foliar fungicide; genotype; environment